DAMPAK INSEKTISIDA NABATI DAUN MIMBA DAN INSEKTISIDA SINTETIK TERHADAP KERUSAKAN DAUN, PERTUMBUHAN, DAN HASIL TANAMAN SAWI (Brassica juncea L.) - Maudodi, Raz Sayyid; Priatmadi, Bambang Joko; Wahdah, Raihani; Saidy, Akhmad Rizalli (EnviroScienteae, 2026)
The decline in mustard (Brassica juncea L.) productivity in recent years has been associated with increasing pest pressure and uncontrolled insecticide use. This study aimed to evaluate the effects of neem leaf–based botanical insecticide and the synthetic insecticide methomyl applied at three spraying frequencies on insect damage intensity, number of leaves, plant height, and fresh weight of mustard. The experiment was arranged in a randomized block design with nested treatments and a separate control. The results showed that the application of both botanical and synthetic insecticides reduced leaf damage intensity and enhanced vegetative growth and fresh weight compared to the control. At 21 days after planting, the neem-based insecticide demonstrated a better ability to suppress pest attack intensity (9.39%) than the synthetic insecticide methomyl (11.29%). The application of methomyl at a spraying interval of three days produced the highest fresh weight (155.08 g) compared to other spraying frequencies.